Montenegro : Technical Assistance Report - Public Investment Management Assessment. (IMF Staff Country Reports; Country Report, 2022)
Public investment is expected to play a significant role in the post-pandemic economic recovery in Montenegro. Due to the importance of the tourism sector, the pandemic has had a deep economic impact. In addition, as government debt already exceeds one hundred percent of GDP, fiscal space to increase public investment is limited. Nevertheless, the completion of the first phase of the Bar-Boljare Highway (BBH), by the end of 2021, should free up public resources within the budget constraint, that could be used for public investments. In this context, a strengthened public investment management (PIM) framework would contribute to maximize its impact on economic growth.